MET Receptor Tyrosine Kinase Controls Dendritic Complexity, Spine Morphogenesis, and Glutamatergic Synapse Maturation in the Hippocampus - Qiu, Shenfeng (J Neurosci, 2014)
The MET receptor tyrosine kinase (RTK), implicated in risk for autism spectrum disorder (ASD) and in functional and structural circuit integrity in humans, is a temporally and spatially regulated receptor enriched in dorsal pallial-derived structures during mouse forebrain development. Here we report that loss or gain of function of MET in vitro or in vivo leads to changes, opposite in nature, in dendritic complexity, spine morphogenesis, and the timing of glutamatergic synapse maturation onto hippocampus CA1 neurons. Consistent with the morphological and biochemical changes, deletion of Met in mutant mice results in precocious maturation of excitatory synapse, as indicated by a reduction of the proportion of silent synapses, a faster GluN2A subunit switch, and an enhanced acquisition of AMPA receptors at synaptic sites. Thus, MET-mediated signaling appears to serve as a mechanism for controlling the timing of neuronal growth and functional maturation. These studies suggest that mistimed maturation of glutamatergic synapses leads to the aberrant neural circuits that may be associated with ASD risk.